Microtubule dynamics in vitro are regulated by the tubulin isotype composition. - Panda, D (1994)
The growing and shortening dynamics of individual bovine brain microtubules at their plus ends at steady state in vitro, assembled from isotypically pure alpha beta II, alpha beta III, or alpha beta IV tubulin dimers, were determined by differential interference contrast video microscopy. Microtubules assembled from the purified alpha beta III isotype were considerably more dynamic than microtubules made from the alpha beta II or alpha beta IV isotypes or from unfractionated phosphocellulose-purified tubulin. Furthermore, increasing the proportion of the alpha beta II isotype in a mixture of the alpha beta II and alpha beta III isotypes suppressed microtubule dynamics, demonstrating that microtubule dynamics can be influenced by the tubulin isotype composition. The data support the hypothesis that cells might determine the dynamic properties and functions of its microtubules in part by altering the relative amounts of the different tubulin isotypes.